Improving program implementation and client engagement in interventions addressing youth homelessness: A meta-synthesis. (January 2021) - Curry, Susanna R.; Baiocchi, Arturo; Tully, Brenda A.; Garst, Nathan; Bielz, Samantha; Kugley, Shannon; Morton, Matthew H.
Highlights: We identified 47 recent studies assessing implementation of homeless youth programs. Most of the qualitative studies identify organizational and staffing challenges. Programs should focus on youth empowerment and anti-paternalist practices. We need increased attention to racial and LGBTQ equity in implementation research. Abstract: Background: Evidence on the effectiveness of programs serving unaccompanied youth experiencing homelessness remains limited and mixed, and we know little about the factors that contribute to participant engagement and program implementation across contexts. Objective: In this meta-synthesis of current findings on youth interventions, we explore the following research questions: (1) What are common programmatic or contextual factors that researchers and/or practitioners identify as contributing to the successful implementation of an intervention for homeless and unstably housed youth? and (2) What programmatic or contextual factors do youth and practitioners identify as hindering successful implementation of an intervention for these youth? Methods: Through systematic searches of academic databases for articles and reports published between 2008 and 2018—as well as identifying unpublished concurrent studies through professional outreach, hand-searching reference lists, and searches of websites—we screened 1602 studies through two levels of blind review. We then inductively coded the resulting 47 studies that met our inclusion criteria to identify patterns and gaps in the existing literature about implementation and engagement in these programs. Results: Most of the studies analyzed took place in urban settings, were based on programs located in the United States, and included a variety of interventions from behavioral health treatment to street outreach and case management. The 47 eligible studies included 3112 youth and 495 staff participants. Only 3 out of the 47 studies explicitly focused on racial or LGBTQ equity. Two primary themes regarding factors that support successful implementation and engagement were identified: (1) Organizational and system-wide policies can shape the quality and duration of interventions, and (2) Staff behaviors and training are paramount to the success of many interventions. With respect to organizational and system-wide policies, many studies highlighted the importance of fostering a developmentally appropriate balance between structure and flexibility; considerations to access including low-barrier options when appropriate; concerns regarding the physical space of the program; and coordination with other agencies, particularly for effective referrals. With respect to staffing behaviors and training, studies highlighted that engagement with youth experiencing homelessness requires strong communication, a youth-centered approach, and a "flexible, non-judgmental orientation, " that allows youth a substantial level of self-determination. Conclusions: Given these findings, this review supports services that emphasize empowerment and anti-paternalism, and increased attention to racial and LGBTQ equity in future exploration of implementation and engagement within programs designed for youth experiencing homelessness.